Environmental Chemicals - Cruz Fernandes, Virgínia (2022)
Funding Information: Funding: This work received financial support from projects UIDB/50006/2020, UIDP/50006/2020, and LA/P/0008/2020 by the Fundação para a Ciência e a Tecnologia (FCT)/Ministério da Ciência, Tecnologia e Ensino Superior (MCTES) through national funds. Virgínia Cruz Fernandes thanks FCT for the financial support through a postdoctoral fellowship (SFRH/BPD/109153/2015).